Melhoria do cetano em óleo diesel : abertura do ciclo da decalina sobre catalisadores de Pt, Ir ou Rh suportados em zeólitas FAU e BEA - Monteiro, Carlos Alberto de Araujo (2011)
Environmental laws and stricter quality specifications have driven the development of technologies for improving the cetane number in diesel fuel. In addition to the saturation of (poly)aromatic compounds, responsible for limited gains, ring opening of at least one ring of (poly)cycloalkane, without loss of yield by cracking, is a promising strategy to maximize this property. Numerous studies have demonstrated the significant performance of Pt, Rh and Ir supported on zeolites for naphthenic ring opening in the hydroconversion of model compounds (naphthalene, tetralin and decalin). This study aimed to systematically assess the role of acid and hydrogenating functions for hydroconversion of decalin. It was also evaluated the effect of activation conditions (calcination and reduction), type of zeolite (Faujasite, FAU, or Beta, BEA), the content and type of metal (Pt, Ir or Rh). The influence of Pt-Ir and Pt-Rh bimetallic systems, as well as the inhibition by H2S, were studied in terms of the performance of these catalysts. For the catalytic precursors prepared, better activity and selectivity to ringopening products were obtained from calcination at 573 K and reduction at 713 K. This performance was consistent with a more homogeneous distribution of metallic particles on the support, and thus greater dispersion of the metallic phase. The reaction steps of ring contraction, ring opening and cracking were consecutive for the hydroconversion of decalin. It is noteworthy that the catalytic systems studied, under the operating conditions employed, yielded up to 45 mol% ring opening products and less than 15 mol% cracking products, at decalin conversions as high as 90 %. The Pt/BEA catalyst presented the best performance, thiotolerance (lower production of cracking products) and thioresistence (selectivity recovery after removal of H2S), followed by the Pt-It/BEA and Ir/BEA catalysts. This study allowed to highlight some peculiarities of the hydroconversion of decalin on noble metal/zeolite catalysts. Although decalin is a saturated molecule, his naphthenic character and probably the presence of a tertiary carbon in its structure, facilitates activation of the molecule directly on the strong acid sites of zeolite, even at relatively moderate temperatures. Thus, it is not necessary to form an olefin on a metal site and undergo subsequent protonation, as in a classical bifunctional mechanism, such as in hydroisomerization and hydrocracking of n-paraffins. However, the hydrogenation component of the catalyst influences the selectivity of the reaction, controlling the process of desorption/adsorption of any intermediate olefins formed. Greater hydrogenation activity implies lower availability of adsorbed carbocations that can be converted to cracking products. This proposition is consistent with the results obtained by varying the type and content of metal, support acidity and poisoning of the hydrogenation sites in the catalysts.